A comparison of alternative systems to catch and kill for mitigating unprovoked shark bite on bathers or surfers at ocean beaches. (15th February 2021) - McPhee, Daryl P.; Blount, Craig; Lincoln Smith, Marcus P.; Peddemors, Victor M.
Abstract: Responses to unprovoked shark bite involve public policies and management approaches that contend with the needs of public safety and the responsibility to protect threatened species. In Australia (Queensland and New South Wales) and South Africa, methods that aim to capture and kill large sharks adjacent to popular beaches are a long-standing approach aimed at reducing the risk of shark bite. This paper reviews non-lethal alternatives to catch and kill methods, and suggests optimal conditions for non-lethal systems that will assist policy makers and beach authorities in choosing public safety responses that can be applied at the ocean beach scale. Deployment needs to be strategic with sufficient knowledge of their likely effectiveness under local conditions. At this stage we believe there is no single approach universally applicable to ocean beaches where unprovoked shark bite occurs, although well considered and locally appropriate mitigation measures can reduce risk. Graphical abstract: Image 1 Highlights: There is no universally applicable approach to mitigating unprovoked shark bite. There is a need to balance public safety with the protection of threatened species. This paper reviews mitigation approaches that do not kill sharks. Considerations for decision makers in deciding mitigation options are discussed.